Implementation of Professional Learning Community among teachers in schools: a systematic literature review - Jalaludin, Afaf Ahmad; Abdul Kadir, Suhaida; Abdullah, Arnida; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2022)
The emergence of the Professional Learning Community (PLC) concept has pioneered the existence and strengthened of the teaching community. PLC formally serves as a professional learning team and through this team, teachers work with a spirit of openness, reflect critically, share their experiences, ideas, expertise, and engage in an ongoing assessment process that fosters deep team learning. So, it is important to look at past studies related to PLC as PLC is among the factors of teacher effectiveness and schools as well. This paper aims to produce a literature review that answers questions such as: i) What are the challenges in the implementation of PLC among teachers; ii) How PLC can develop the innovation of teachers; and iii) How can the Professional Learning Community develop teacher competencies? The systematic literature review method is used as the methodology in this paper. Articles from 2018 to 2022 related to PLC were searched from three main databases, namely, Scopus, Web of Science, and Google Scholar. The finding show a total of 384 articles were identified; however, after screening based on the inclusion and exclusion criteria, only 76 articles were used as final articles for review related to PLC challenges and the impact of PLC implementation on innovation development and teacher competencies. The results of this literature review are beneficial for future studies on PLC and can be a guideline for higher authorities in the field of education, especially the Ministry of Education, to design quality PLC programs that can enhance teacher professionalism and, in turn, improve student learning. It is recommended that a more detailed implementation of PLC be considered in further studies, as its strategy and effectiveness still have not been sufficiently examined.